Universal unilateral electro-spinning/spraying strategy to construct water-unidirectional Janus membranes with well-tuned hierarchical micro/nanostructures. Issue 3 (12th December 2019) - Yan, Linlin; Yang, Xiaobin; Long, Jun; Cheng, XiQuan; Pan, Duo; Huang, Yifeng; Shao, Lu
Abstract : Janus membranes with hierarchical micro/nanostructures were constructed by a unilateral electro-spinning/spraying strategy to realize water directional transportation. Abstract : Janus membranes (JMs) with hierarchical micro/nanostructures were constructed by unilaterally electro-spinning/spraying a hydrophobic polymer on various hydrophilic porous substrates for liquid manipulation/rectification. The membrane geometry and liquid transport behaviors can be delicately tuned. Our novel universal strategy can be extended to diverse hydrophobic porous substrates.